2020
DOI: 10.1021/acs.est.0c03803
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Time, Taxonomy, and Selective Antimicrobials to Antibiotic and Multidrug Resistance in Wastewater Bacteria

Abstract: The use of nontherapeutic broad-spectrum antimicrobial agents triclosan (TCS) and benzalkonium chloride (BC) can contribute to bacterial resistance to clinically relevant antibiotics. Antimicrobial-resistant bacteria within wastewater may reflect the resistance burden within the human microbiome, as antibiotics and pathogens in wastewater can track with clinically relevant parameters during perturbations to the community. In this study, we monitored culturable and resistant wastewater bacteria and cross-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…A few studies have looked at the impact of BKC treatment on complex biofilm communities. Gray et al ( 2021 ) showed that bacterial isolates from water treatment plants that were able to grow on 250–500 mg l −1 BKC accounted for 0.2% of the overall culturable communities and were mainly Pseudomonas spp. A high proportion of these isolates with colistin resistance were observed, but no direct link between BKC insusceptibility and colistin resistance was demonstrated.…”
Section: Benzalkonium Chloride and Bacterial ‘Resistance’mentioning
confidence: 99%
“…A few studies have looked at the impact of BKC treatment on complex biofilm communities. Gray et al ( 2021 ) showed that bacterial isolates from water treatment plants that were able to grow on 250–500 mg l −1 BKC accounted for 0.2% of the overall culturable communities and were mainly Pseudomonas spp. A high proportion of these isolates with colistin resistance were observed, but no direct link between BKC insusceptibility and colistin resistance was demonstrated.…”
Section: Benzalkonium Chloride and Bacterial ‘Resistance’mentioning
confidence: 99%
“…In response to the accelerating rise in antimicrobial resistance, great efforts have been made to develop methods for the rapid detection of AMR bacteria. ,, The commonly used methods for detecting AMR bacteria in aquatic environments (Table S5) either rely on culturing bacteria, , which can identify only a small fraction of the total diversity present in samples, or on postgenomic techniques such as metagenomics and metatranscriptomics, which cannot directly link AMR to active hosts from functional phenotypes. , In addition, these methods are not suitable for on-site monitoring of microbial changes in aquatic environments because of the heavy preparative work and the requirement of in-depth analysis of the huge amount of data . Although a tyrosine signal amplification-fluorescence in situ hybridization-fluorescence-activated cell sorting (TSA-FISH-FACS) method has been developed and allows for coupling with high-throughput sequencing (Table S5), it is very complex and limited to the quantification and detection of bacteria carrying vancomycin resistance genes …”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics refer to a class of chemical substances or fully chemically synthesized substances produced by living organisms (mostly microorganisms, including bacteria, fungi, and actinomycetes spp.) during their life processes, which have antipathogenic activity [1]. The discovery and application of antibiotics is one of the greatest medical discoveries of the 20th century [2][3].…”
Section: Introductionmentioning
confidence: 99%